Snakes of Italy : herpetological treatise on the biology and iconography of Italian ophidians - Achille, Gabriele (SpringerBriefs in Animal Sciences,, 2015)
This book offers a comprehensive review of the biology of snakes, focusing on Italian species. The snakes of Italy belong to the two families Colubridae and Viperidae, and for each species the systematic classification and chorology including distribution maps are presented. Furthermore, readers will learn how to carry out field studies, how to handle snakes and how to photograph them. The book concludes with a chapter on the iconography of historical Italian snakes and their importance in popular science, and one on myths and legends. This SpringerBriefs volume will appeal to herpetologists and technical staff. The section on iconography may also be of interest to museum staff.